Simple Solvent Engineering for High-Mobility and Thermally Robust Conjugated Polymer Nanowire Field-Effect Transistors - Jeon, Gyeong G.; Lee, Myeongjae; Nam, Jinwoo; Park, Wongi; Yang, Minyong; Choi, Jong Ho; Yoon, Dong Ki; Lee, Eunji; Kim, Bongsoo; Kim, Jong H. (ACS Applied Materials and Interfaces, 2018)
Electron donor (D)-acceptor (A)-type conjugated polymers (CPs) have emerged as promising semiconductor candidates for organic field-effect transistors. Despite their high charge carrier mobilities, optimization of electrical properties of D-A-type CPs generally suffers from complicated post-deposition treatments such as high-temperature thermal annealing or solvent-vapor annealing. In this work, we report a high-mobility diketopyrrolopyrrole-based D-A-type CP nanowires, self-assembled by a simple but very effective solvent engineering method that requires no additional processes after film deposition. In situ grown uniform nanowires at room temperature were shown to possess distinct edge-on chain orientation that is beneficial for lateral charge transport between source and drain electrodes in FETs. FETs based on the polymer nanowire networks exhibit impressive hole mobility of up to 4.0 cm2 V-1 s-1. Moreover, nanowire FETs showed excellent operational stability in high temperature up to 200 °C because of the strong interchain interaction and alignment.
Keywords: Conjugated polymer nanowires; Diketopyrrolopyrroles; Interchain interactions; Operational stability; Post deposition treatment; Solvent engineering; Solvent-vapor annealing; Source and drain electrodes; conjugated polymers; Hansen solubility parameters; high-mobility; nanowires; organic field-effect transistors; stability